USAHA PENINGKATAN KETERAMPILAN PEMECAHAN MASALAH MELALUI MODEL PROBLEM BASED LEARNING DI KELAS V SDN BABATAN V/460 SURABAYA - Wardani, Duhita Savira (COLLASE (Creative of Learning Students Elementary Education), 2020)
Abstract The background of this study was the low of students’ problem solving skills caused by the teacher using conventional method on science subject so there were not active student activity in finding and solving problems. This study addressed to cope students’ problem in problem solving skills on  classroom by implementing Problem Based Learning model. The study followed a classroom action research through three stages namely planning, implementing and observing, and reflecting action. This research subject to fifth grade SD Babatan V/460 Surabaya on science subject. This research was conducted in two cycles consisting of two meetings for each. The data were gathered using observation, tests, and questionnaire. The result of this study showed the implementation of the Problem Based Learning Model on science subject could improve students’ problem solving skills. It was indicated by an enhancement in the average value of problem solving skills test. Furthermore, the application of this model can also increase students’ learning outcomes, teacher activity of learning, students activity of learning, and students’ responses. Thus, teachers can apply this Problem Based Learning model to increase the activitiy of learning and thinking skills in problem solving of their primarily students.Keywords: Problem Based Learning Model (PBL), Problem Solving Skills, Science.